Antidepressant-like activity of hyperforin and changes in BDNF and zinc levels in mice exposed to chronic unpredictable mild stress - Szewczyk, Bernadeta; Pochwat, Bartłomiej; Muszyńska, Bożena; Opoka, Włodzimierz; Krakowska, Agata; Rafało-Ulińska, Anna; Friedland, Kristina; Nowak, Gabriel (Behavioural brain research, 2019)
Chronic unpredictable mild stress (CUMS) - a rodent model of depression mimics a variety of neurochemical and behavioral alterations similar to those seen in human depression. This study evaluated the antidepressant activity of hyperforin in the CUMS model using fluoxetine (FLX) as a reference drug. The antidepressant-like effects of hyperforin and FLX were evaluated in the tail suspension test (TST), forced swim test (FST), and splash test (SPT). CUMS induced an increase in immobility time in mice (pro-depressive effects) in the FST and TST. CUMS-induced changes were reversed by chronic treatment with hyperforin (2.5 and 5 mg/kg), as well as FLX (10 mg/kg). SPT results revealed a decrease in the frequency and duration of grooming in stressed mice. These effects were normalized by hyperforin (5 mg/kg) and FLX treatment. Hyperforin (2.5 mg/kg) only reversed the CUMS-induced deficits related to the frequency of grooming. CUMS also caused a decrease in zinc concentration in the frontal cortex (FC) and hippocampus (Hp) of mice; hyperforin (2.5 mg/kg) increased zinc concentration in the Hp of control rats. CUMS also induced a decrease in BDNF protein levels in the FC and Hp, while decreasing the pCREB/CREB ratio only in the Hp. Hyperforin (2.5 and 5 mg/kg) reversed the CUMS-induced reduction of BDNF only in the Hp. Our results demonstrate the antidepressant-like activity of hyperforin in the CUMS model in mice and the possible involvement of hippocampal BDNF/zinc alterations in this activity.